Suggested: (x-y)3+(y-z)3+(z-x)3 - factorise (x-y)3+(y-z)3+(z-x)3 - prove that (x+y)3+(y+z)3+(z+x)3-3(x+y)(y+z)(z+x)=2(x3+y3+z3-3xyz) - (x-y)^3+(y-z)^3+(z-x)^3/9(x-y)(y-z)(z-x) - x^3+y^3+z^3-3xyz=1/2(x+y+z)((x-y)^2+(y-z)^2+(z-x)^2) - यदि x+y+z=0 तो दिखाइये कि x^(3)+y^(3)+z^(3)=3xyz - x+y+z=1 x^2+y^2+z^2=2 x^3+y^3+z^3=3 - u=x+y+z v=x^2+y^2+z^2-2xy-2yz-2zx z=x^3+y^3+z^3-3xyz relation between uvw - find the value of x^3+y^3+z^3-3xyz if x2+y2+z2=83 and x+y+z=15 - 13.if x+y+z=0 show that x^(3)+y^(3)+z^(3)=3xyz - 12.verify that x^(3)+y^(3)+z^(3)-3xyz=(1)/(2)(x+y+z) (x-y)^(2)+(y-z)^(2)+(z-x)^(2) - (x-y)3+(y-z)3+(z-x)3=30 - (x y)3+(y z)3+(z x)3 Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.